The role of metal sulfates in thermochemical sulfate reduction (TSR) of hydrocarbons: Insight from the yields and stable carbon isotopes of gas products - Lu, Hong; Greenwood, Paul; Chen, Tengshui; Liu, Jinzhong; Peng, Ping’an (Organic geochemistry, 2011)
The mechanism of thermochemical sulfate reduction (TSR) was investigated by separately heating n-C 24 with three different sulfates (CaSO 4, Na 2SO 4, MgSO 4) in sealed gold tubes at 420 °C and measuring the stable carbon isotope values of hydrocarbon (C 1–C 5) and non-hydrocarbon (CO 2) products. Extensive TSR was observed with the MgSO 4 reactant as reflected by increasing concentrations of H 2S, 13C depleted CO 2 and relatively low concentrations of H 2 (compared to the control). H 2S yields were already very high at the first monitoring time (12 h) when the temperature had just reached 420 °C, suggesting that TSR had commenced well prior to this temperature. Only trace amounts of n-C 24 and secondary C 3–C 5 alkanes were detected at 12 h, reflecting the efficient TSR utilization of the reactant and lower molecular weight alkane products. Ethane levels were still relatively high at 12 h, but declined thereafter as it was subject to TSR in the absence of higher molecular weight alkanes which had already been utilized. Methane yields were consistently high throughout the 48 h MgSO 4 treatment. The temporal decrease in the concentrations of alkanes available for TSR may also contribute to the sharp enhancement of CO 2 after 36 h. Absence or dampening of the molecular and isotopic trends of MgSO 4 TSR was observed with Na 2SO 4 and CaSO 4 respectively, directly reflecting the levels of TSR reached using these sulfate treatments. For all treatments, the δ 13C values of C 1–5 n-alkanes showed an increase with both molecular weight and treatment time. MgSO 4 TSR led to a 5–10‰ increase in the δ 13C values of the C 1–C 5 hydrocarbons and a 20‰ decrease in the δ 13C value of CO 2. The significant 13C depletion of the CO 2 may be due to co-production of 13C enriched MgCO 3, although this remains unproven as the δ 13C of MgCO 3 was not measured. The difference in the δ 13C values of ethane and propane (Δ δ 13C EP) increased in magnitude with the degree of TSR, and this trend could be used to help evaluate the occurrence and extent of TSR in subsurface gas reservoirs.